Technology Acceptance in Augmented Reality - Yuniarto, Dwi; Helmiawan, Muhammad Agreindra; Firmansyah, Esa (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
Augmented Reality is now used in many fields, including in terms of helping the learning process. The purpose of this research is to know the effect of interrelated based on Technology Acceptance model, namely Perceived Usefulness, Perceived Easy to Use, Behavioral Intention Use, and Actual System Use on the use of Augmented Reality based card game. This research resulted that hypothesis in this research accepted after going through data analysis process from questionnaire result. A huge interest in the use of Augmented Reality-based games as actual technology as a factor in whether or not the game is accepted. Users, viewed in terms of ease of use and the benefits posed by the game is also very influential on the acceptance of games based on Augmented Reality.